1984
DOI: 10.1136/jnnp.47.1.51
|View full text |Cite
|
Sign up to set email alerts
|

Effect of indomethacin on cerebral blood flow, carbon dioxide reactivity and the response to epoprostenol (prostacyclin) infusion in man.

Abstract: SUMMARY Cerebral blood flow (CBF) has been measured using a non-invasive Xenon'33 clearance technique in six normal subjects after 2 days pretreatment with oral indomethacin at a dose of 100 mg/day. The results were compared with placebo given in a double blind balanced cross-over design. Indomethacin was found to result in a reduction in resting CBF of about 25% but the reactivity of the cerebrovascular circulation to carbon dioxide was preserved at normal levels. Infusions of epoprostenol (prostacyclin, PGI2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 19 publications
3
10
0
Order By: Relevance
“…In one study no control group received hypercapnia; a significant increase in CBF was seen with a very modest increase in CO 2 concentration from 5.0 to 5.5 kPa, but this may represent a nonspecific response to the stress of the mask and the CO 2 . 13 Furthermore, without a control group it is unclear whether the response to hypercapnia was reduced compared with normal subjects, as the trend in our study suggested, or was unaltered as found by Pickles et al 14 However, other studies revealing conflicting results induced greater changes in end-tidal CO 2 concentrations, similar to those attained in our study, and used ade- Abbreviations as in Table 1. Standard deviations are shown in parentheses.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…In one study no control group received hypercapnia; a significant increase in CBF was seen with a very modest increase in CO 2 concentration from 5.0 to 5.5 kPa, but this may represent a nonspecific response to the stress of the mask and the CO 2 . 13 Furthermore, without a control group it is unclear whether the response to hypercapnia was reduced compared with normal subjects, as the trend in our study suggested, or was unaltered as found by Pickles et al 14 However, other studies revealing conflicting results induced greater changes in end-tidal CO 2 concentrations, similar to those attained in our study, and used ade- Abbreviations as in Table 1. Standard deviations are shown in parentheses.…”
Section: Discussionsupporting
confidence: 64%
“…- 14 In addition, in some animal models indomethacin reduces the cerebral vasodilatory response to hypercapnia, 7 ' 810 although studies in humans have revealed conflicting results.…”
mentioning
confidence: 99%
“…1). In contrast, Pickles et al (1984) reported a reduced basal CBF without any concurrent changes in cerebrovascular CO 2 reactivity in six participants following 2 days of INDO oral administration (100 mg day -1 ). However, in that study, participants were given 50 mg of INDO the morning of the experiment, whilst the present and other previous studies (Bruhn et al 2001;Eriksson et al 1983;Fan et al 2010;Ivancev et al 2009;Markus et al 1994;St Lawrence et al 2002;Wennmalm et al 1983;Xie et al 2006Xie et al , 2009 have assessed the effect of INDO on the cerebrovascular CO 2 reactivity following a single larger dose of INDO (100 mg) 90 min prior to measurement.…”
Section: Influence Of Indomethacin On Cerebrovascular Reactivity To Cmentioning
confidence: 77%
“…However, in that study, participants were given 50 mg of INDO the morning of the experiment, whilst the present and other previous studies (Bruhn et al 2001;Eriksson et al 1983;Fan et al 2010;Ivancev et al 2009;Markus et al 1994;St Lawrence et al 2002;Wennmalm et al 1983;Xie et al 2006Xie et al , 2009 have assessed the effect of INDO on the cerebrovascular CO 2 reactivity following a single larger dose of INDO (100 mg) 90 min prior to measurement. Accordingly, these methodological differences make it difficult to compare the findings of the Pickles et al (1984) study. Nishimura et al (1987) have previously found a reduction in the arterial-to-internal venous jugular PCO 2 difference during 5-15 min of hypoxic exposure in healthy humans.…”
Section: Influence Of Indomethacin On Cerebrovascular Reactivity To Cmentioning
confidence: 98%
“…In addition, due to the reduction in arterial blood pressure, the net effect of prostacyclin in this study was a reduction in the cerebral perfusion pres sure. Other studies have shown that prostacyclin may cause both a reduction in cerebral blood flow [38] and cerebral perfusion pressure [39]. In this study, prostacyc lin caused a reduction in arterial oxygen tension and for the majority of patients studied a reduction in cardiac output.…”
Section: Discussionmentioning
confidence: 64%